Պատմութիւն Սրբոյն Թեկղի եւ վկայաբանութիւն Ս. Թադէոսի եւ Սանդխտոյ կուսին. Համեմատութիւն եւ բնագրական նկատողութիւններ - Կալցոլարի, Վալենտինա («Նաիրի» հրատ.)
This paper deals with the question of the relationship between the Armenian version of the apocryphal Acts of Paul and Thecla and the Armenian Martyrdom of Thaddeus and Sanduxt. N. Akinean raised the hypothesis of a possible influence of the first text on the second one in an article published posthumously in Handēs Amsōreay in 1970. He did not give any commentary, but simply put some parallels of the two works in a synoptic presentation
Keywords: Բանասիրութիւն; Վկայաբանութիւն